Artificial Intelligence Usage Intention for Sustainable Development: A Neo ESG Perspective Using Hybrid Methods - Nguyen, Vo Dinh Cao; Do, Huu Tam (Sinkron : jurnal dan penelitian teknik informatika, 2026)
This study finds that the rapid development of artificial intelligence, together with the growing pressure to implement environmental, social, and governance principles, has driven firms to search for new models of sustainable governance. However, prior research has lacked empirical evidence on the role of artificial intelligence usage intention within a dynamic environmental, social, and governance framework and its interplay with social and environmental dimensions. To address this gap, the study reconceptualizes environmental, social, and governance by representing governance through artificial intelligence, the social dimension through diversity, equity, and inclusion, and the environmental dimension through exploitative green innovation and exploratory green innovation. Based on survey data from 357 firms, a hybrid methodological approach employing partial least squares structural equation modeling, artificial neural networks, and fuzzy set qualitative comparative analysis is applied. The results reveal that diversity, equity, and inclusion has the strongest effect on sustainable development (β = 0.533; t = 13.061; p < 0.001), followed by artificial intelligence, while exploitative green innovation plays a supportive role and exploratory green innovation shows no significant impact. Artificial neural networks validate these findings with stable predictive accuracy, while fuzzy set qualitative comparative analysis identifies multiple alternative pathways to sustainability (equifinality). The study contributes by positioning artificial intelligence as a new governance mechanism within environmental, social, and governance and highlighting the central role of diversity, equity, and inclusion, while also offering strategic guidance for integrating technological and social factors to foster sustainable development.